STAP-2 positively regulates FcεRI-mediated basophil activation and basophil-dependent allergic inflammatory reactions. (6th February 2019) - Kashiwakura, Jun-ichi; Yamashita, Shinsuke; Yoshihara, Mari; Inui, Kyosuke; Saitoh, Kodai; Sekine, Yuichi; Muromoto, Ryuta; Kitai, Yuichi; Oritani, Kenji; Matsuda, Tadashi
Abstract: Basophils are an important cell type in the regulation of Th 2 immune responses. Recently, we revealed that signal-transducing adaptor protein-2 (STAP-2) negatively regulates mast cell activation via FcεRI. However, the role of STAP-2 in basophil maturation and activation remained unclear. In this study, we demonstrated the normal development of basophils in STAP-2-deficient (STAP-2 −/− ) mice. We also demonstrated in vitro normal basophil differentiation and FcεRI expression in STAP-2 −/− mice, suggesting that STAP-2 is dispensable for basophil maturation. Using bone marrow-derived cultured basophils (BMBs), we showed that degranulation and cytokine production of STAP-2 −/− BMBs were lower than those of wild-type (WT) BMBs upon stimulation with IgE/Ag. In accordance with the reduction of degranulation and cytokine production, phosphorylation of several signal molecules such as Lyn, PLC-γ2 and Erk was reduced in STAP-2 −/− BMBs after stimulation via FcεRI. Finally, it was observed that IgE-dependent chronic allergic inflammation of STAP-2 −/− mice was significantly inhibited compared with WT mice. Taken together, we conclude that STAP-2 is an adaptor molecule that positively regulates FcεRI-mediated basophil activation and basophil-dependent allergic inflammatory reactions. Abstract : STAP-2 positively regulates basophil activation